Molecular epidemiology of Escherichia coli isolated from urinary tract infections in inpatients and outpatients in Gauteng, South Africa - Kock, Martha Magdalena (University of Pretoria, 2022)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2021.